The application of Google Classroom on teaching writing in post Covid-pandemic era - Destiyana, Destiyana; Lengkanawati, Nenden Sri (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2023)
The existence of Google Classroom as an instructional medium is a new thing in the education sector, which is expected to make the learning and teaching process easier, especially in teaching writing. This study investigated the application of google classroom in Teaching Writing in one of Senior High School in Indonesia in post-pandemic era. The research objectives were intended to describe the implementation of google classroom in teaching writing for Senior High School students after Covid-19 pandemic, to identify the teacher and students’ roles in google classroom, to describe strengths and weaknesses of the implementation of google classroom. The design of the research was descriptive qualitative. The data were collected through observation, interview, and documentation. The research findings showed that the methods used by the teacher were planning, drafting, and editing. Moreover, the roles of teachers were as controller, observer, organizer, explainer and evaluator, while students’ roles are as processor, performer, and listener. The strengths of the implementation of google classroom in teaching writing for Senior High School students after Covid-19 pandemic era because of its practicality, feature, and simplicity. On the other hand, its weaknesses were low internet connection, difficulties in features of google classroom, and difficulties in evaluation. This study suggested that Google Classroom is a relatively new technology in Indonesia, and there is not much research into its applications in language teaching and learning. This research, therefore, lays a foundation for further investigations into this field. To start with, the implementation of Google Classroom is perfectly feasible. Secondly, technology just plays a supportive part, and teachers should be responsive to students’ activities. The most favourable feature of Google Classroom among students is the use of Google Docs for writing assignments, giving and receiving comments and feedbacks.